Oscillation of the per capita growth rate - Baghdad Science Journal (مجلة بغداد للعلوم, 2005)
in this paper cquations of the per capita growth rate are considered sufficient conditions for oscillation of all solutions are obtained the asymptotie behavior of the nonoscillatory solution of all souliotions are obtained